(untitled) (Scientific journal of the Fergana State University, 2024)
The conceptual sphere is an important issue to be studied in linguistics, and attention to conceptual analysis is increasing in research conducted on the analysis of literary texts. This article is devoted to the expression of the concept of love in the work of the scientist and poet Siddique Momin using poems included in the poet’s collection “Biomaidon”. The concept of love used in twenty-one places in the collection is explained